A Gricean Theory of Malaprops. (14th July 2017) - Unnsteinsson, Elmar
Abstract: Gricean intentionalists hold that what a speaker says and means by a linguistic utterance is determined by the speaker's communicative intention. On this view, one cannot really say anything without meaning it as well. Conventionalists argue, however, that malapropisms provide powerful counterexamples to this claim. I present two arguments against the conventionalist and sketch a new Gricean theory of speech errors, called the misarticulation theory. On this view, malapropisms are understood as a special case of mispronunciation. I argue that the Gricean theory is supported by empirical work in phonetics and phonology and, also, that conventionalism inevitably fails to do this work justice. I conclude, from this, that the conventionalist fails to show that malapropisms constitute a counterexample to a Gricean theory.